Mortality related to invasive infections, sepsis, and septic shock in critically ill children in Australia and New Zealand, 2002–13: a multicentre retrospective cohort study. Issue 1 (January 2015) - Schlapbach, Luregn J; Straney, Lahn; Alexander, Janet; MacLaren, Graeme; Festa, Marino; Schibler, Andreas; Slater, Anthony; for the ANZICS Paediatric Study Group, †
Summary Background Severe infections kill more than 4·5 million children every year. Population-based data for severe infections in children requiring admission to intensive care units (ICUs) are scarce. We assessed changes in incidence and mortality of severe infections in critically ill children in Australia and New Zealand. Methods We did a retrospective multicentre cohort study of children requiring intensive care in Australia and New Zealand between 2002 and 2013, with data from the Australian and New Zealand Paediatric Intensive Care Registry. We included children younger than 16 years with invasive infection, sepsis, or septic shock. We assessed incidence and mortality in the ICU for 2002–07 versus 2008–13. Findings During the study period, 97 127 children were admitted to ICUs, 11 574 (11·9%) had severe infections, including 6688 (6·9%) with invasive infections, 2847 (2·9%) with sepsis, and 2039 (2·1%) with septic shock. Age-standardised incidence increased each year by an average of 0·56 cases per 100 000 children (95% CI 0·41–0·71) for invasive infections, 0·09 cases per 100 000 children (0·00–0·17) for sepsis, and 0·08 cases per 100 000 children (0·04–0·12) for septic shock. 260 (3·9%) of 6688 patients with invasive infection died, 159 (5·6%) of 2847 with sepsis died, and 346 (17·0%) of 2039 with septic shock died, compared with 2893 (3·0%) of all paediatric ICU admissions. Children admitted with invasive infections, sepsis, and septic shock accounted for 765 (26·4%) of 2893 paediatric deaths in ICUs. Comparing 2008–13 with 2002–07, risk-adjusted mortality decreased significantly for invasive infections (odds ratio 0·72, 95% CI 0·56–0·94; p=0·016), and for sepsis (0·66, 0·47–0·93; p=0·016), but not significantly for septic shock (0·79, 0·61–1·01; p=0·065). Interpretation Severe infections remain a major cause of mortality in paediatric ICUs, representing a major public health problem. Future studies should focus on patients with the highest risk of poor outcome, and assess the effectiveness of present sepsis interventions in children. Funding National Medical Health and Research Council, Australian Resuscitation Outcomes Consortium, Centre of Research Excellence (1029983).